KHON - กล่ำเจริญ อมรา (วารสารสถาบันวัฒนธรรมและศิลปะ, 2018)
The objectives of this research are to protect a Thai classical dance drama, Khon, which is one of the Thai cultural heritage and local wisdom, by collecting and storing the information concerning this performance art; and to preserve it, under the community engagement, by providing its archives and nominating it as one of the world intangible cultural heritage to UNESCO when Thailand joins the convention for the safeguarding of the intangible cultural heritage in the future. The research methodology is conducted by studying the documents and research papers concerned, making a field trip to cooperate with the authorities concerned, interviewing the people concerned, and observing the styles found in performing Khon in the present. It is found that Khon has been preserved, inherited, and developed continually from the Ayutthaya to the Rattanakosin Periods under the patronage of a monarch. Traditionally, Khon was one of the royal performance arts. Later it had been extended to the commoners. Up until now, the authority being in charge of this performing art has been the Fine Arts Department, Ministry of Culture. In terms of education, a college of Dramatic Arts was established in 1934. Nowadays there are 12 colleges of Dramatic Arts under the supervision of the Banditpatanasilpa Institute, Ministry of Culture which provide performing and musical arts education from the fundamental to tertiary levels. At the present time, the community engagement in preserving and inheriting Khon performing arts has been found in the Khon performance shows organized and provided by the Crown Property Bureau, Queen Sirikit, various foundations, educational institutions, public agencies, and people interested. Being considered as the Thai cultural heritage and local wisdom among Thai ways of life, a kind of performing arts with a combination of various branches of sciences and art genres, and a unique and advanced performing art which is the symbol of the Thainess, Khon should be nominated as one of the world intangible cultural heritage to UNESCO.